Chitin–glucan complex production by Komagataella pastoris: Downstream optimization and product characterization. (5th October 2015) - Farinha, Inês; Duarte, Paulo; Pimentel, Ana; Plotnikova, Evgeniya; Chagas, Bárbara; Mafra, Luís; Grandfils, Christian; Freitas, Filomena; Fortunato, Elvira; Reis, Maria A.M.
Highlights: CGC was extracted from Komagataella pastoris biomass using a solvent-free procedure. CGC had a β-glucan:chitin molar ratio of 75:25 and a molecular weight of 4.9 × 10 5 Da. DRX analyses revealed the presence of α-chitin. CGC had a crystallinity index of 50% and it decomposed at 315 °C. K. pastoris CGC is an attractive alternative to crustacean chitin derived-products. Abstract: Purified chitin–glucan complex (CGCpure ) was extracted from Komagataella pastoris biomass using a hot alkaline treatment, followed by neutralization and repeated washing with deionized water. The co-polymer thus obtained had a β-glucan:chitin molar ratio of 75:25 and low protein and inorganic salts contents (3.0 and 0.9 wt%, respectively). CGCpure had an average molecular weight of 4.9 × 10 5 Da with a polydispersity index of 1.7, and a crystallinity index of 50%. Solid-state NMR provided structural insight at the co-polymer. X-ray diffraction suggests that CGCpure has α-chitin in its structure. CGCpure presented an endothermic decomposition peak at 315 °C, assigned to the degradation of the saccharide structures. This study revealed that K. pastoris CGC has properties similar to other chitinous biopolymers and may represent an attractive alternative to crustacean chitin derived-products, being a reliable raw material for the development of new/improved pharmaceutical, cosmetic or food products.